Multinationals' profit response to tax differentials: Effect size and shifting channels - Jost H. Heckemeyer; Michael Overesch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper provides a quantitative review of the empirical literature on profit-shifting behavior of multinational firms. We synthesize the evidence from 25 studies and find a substantial response of profit measures to international tax rate differentials. Accounting for misspecification biases by means of meta-regressions, we predict a tax semi-elasticity of subsidiary pre-tax profits of about 0.8. Moreover, we disentangle the tax response by means of financial planning from the transfer pricing and licensing channel. Our results suggest that transfer pricing and licensing are the dominant profit-shifting channel.
urn:nbn:de:bsz:180-madoc-340498
Keywords: H25; H26; H32; 330; Profit Shifting; Multinational Firm; Corporate Income Tax; Meta-Analysis